Hip Pain in Nonambulatory Children with Type-I or II Spinal Muscular Atrophy. Issue 3 (14th July 2022) - Hanna, Rewais B.; Nahm, Nick; Bent, Melissa A.; Sund, Sarah; Patterson, Karen; Schroth, Mary K.; Halanski, Matthew A.
Abstract : Background: The purpose of the present study was to define the prevalence of hip pain in nonambulatory children with spinal muscular atrophy (SMA) (type I or II) treated with aggressive medical management, prior to widespread use of disease-modifying therapies (DMTs). Methods: A retrospective chart review (1993 to 2017) was performed on children diagnosed with SMA to identify subjective reports of hip pain and associated interventions, while radiographs were evaluated to assess hip instability and spinal deformity. Results: Seventy-two patients (33 with type I and 39 with type II) met the inclusion criteria. Hip pain was more frequent in type-II SMA (49% versus 12%; p = 0.001). Seventeen percent of the patients with 2 copies of the SMN2 (survival motor neuron 2) gene, 53% of patients with 3 copies, and 1 of the 2 patients with 4 copies reported hip pain. Nearly all patients had abnormal findings on hip radiographs made at the onset of pain or at the latest follow-up; however, no patient with type-I and 18% of those with type-II SMA had pain that was severe enough to undergo invasive intervention (p = 0.01). The intervention reduced the pain in most of those patients but completely eliminated it in only 1 patient. No significant differences were found with respect to the mean age at the onset of scoliosis, the mean age at the time of scoliosis surgery, or whether insertion of growing rods or posterior spine fusion was performed between those with and without hip pain requiring invasive treatment. Conclusions: This study is, to our knowledge, the largest investigation to date to assess hip pain among nonambulatory children with type-I or type-II SMA and suggests that symptoms rather than radiographs be utilized to direct care. These data will be crucial in assessing any effects that the new DMTs have on the natural history of hip pathology and pain in nonambulatory patients with SMA. Level of Evidence: Prognostic Level IV . See Instructions for Authors for a complete description of levels of evidence.